Potential Distribution of Tropical Native Gayam Forest Tree (Inocarpus fagifer Forst.) to Cope with the Drought Hazards in Yogyakarta Landscape - Wibowo, Andri; Utomo, Suyud Warno (Jurnal Manajemen Hutan Tropika, 2026)
Yogyakarta's landscape is known for having experienced drought hazard. At the same time, there is a native tropical tree that has the ability to store the water and cope with the emerging drought. In this regard, this study is aiming to evaluate the potential distribution of the tropical native gayam forest tree (Inocarpus fagifer Forst.) to cope with the drought in the Yogyakarta landscape. Samplings of I. fagifer covered four districts (Sleman, Kulonprogo, Bantul, and Gunung Kidul) and one city (Yogyakarta City) and implemented from January to March 2025. The potential distribution was estimated using MaxEnt. The drought was estimated using remote sensing. The resulting model gained an AUC of 0.804, confirming that I. fagifer can adapt to low rainfall and has the potential to inhabit areas with drought. Bantul, Sleman, and Kulonprogo were districts where the I. fagifer potential distribution areas exceeded almost five to seven times the drought areas. This information can be used as a baseline and recommendation from village to district levels to start to mainstream and disseminate the planting of tropical native trees as a nature-based solution to cope with the drought hazards across Yogyakarta's landscape.